The Impact of Brand Experience on Brand Loyalty: Investigating the Mediating Roles of Hedonic Value and Customer Satisfication - Abd Halim, Nur Iffah; Hishammudin, Nurin Nazihah; Che Ahmat, Nur Hidayah; Ahmad Ridzuan, Ahmad Hidayat (Centre For Tourism Planning and Development, 2024)
This study investigates the mediating roles of hedonic value and customer satisfaction in influencing the associations between brand experience and brand loyalty. Using a quantitative online survey method, we gathered 384 completed responses from young consumers currently studying at universities. Structured equation modelling and bootstrapping were used to test the hypotheses. The findings yielded significant associations between the variables. The significant mediating roles of hedonic value and customer satisfaction are worth noting. This study expands the existing literature by investigating the impact of brand experience on brand loyalty and the critical roles of hedonic value and customer satisfaction. The study findings have implications for the coffee shop owners to stimulate the overall experience of young consumers as an emerging market. The coffee shop owners can expand their business by opening more coffee shop outlets inside the higher education institutions so their coffee brand can easily reach the target market.